Sustainability of halal food industry: an ethical perspective - Nordin, Fatin Nur Majdina; Wan Mohamed Radzi, Che Wan Jasimah; Awang, Mohd Daud (Universiti Islam Pahang Sultan Ahmad Shah, 2022)
This paper attempts to have an overview of the implementation of ethics in the sustainable halal food industry as it may affect the halal industry directly and indirectly. Ethics is a fundamental prerequisite to action as individuals and society have a belief system that acknowledges the importance of natural development to human development will they engage in actions for sustainable development. The implementation of ethics in the halal food industry is reviewed in terms of the aspects of authority, manufacturer, and consumer. There are four main aspects of ethics reviewed in this study, namely the knowledge, relation, social impact and lifestyle. Further investigation digests the knowledge and relation between halal and sustainability, analysis on social impact, and lifestyle change may contribute towards sustainable halal food industry. In short, this paper generates ideas for researchers to conduct other researches that may lead to the sustainable halal food industry in Malaysia.